Peran Guru dalam Meningkatkan Rasa Percaya Diri Anak Usia Dini di Tk Jasa Mekar Mandiri Kabupaten Seluma - Awalia, Jenepa; Nurwita, Syisva; Sari, Rika Partika (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to determine the role of teachers in improving children's independence (descriptive quality in TK Jasa Mekar Mandiri Seluma Regency). This research is a qualitative descriptive research. Data were collected through observation, interviews, and documentation. The main subjects in this study were teachers and students at Jasa Mekar Mandiri Kindergarten, Seluma Regency. The results showed that: The role of teachers in increasing early childhood self-confidence in TK Jasa Mekar Mandiri Seluma Regency is First, the role of educating is carried out by means of teachers being able to arouse children's interest, encourage and teachers must try to motivate children to try children to be more courageous and confident in themselves. Second, the role of teaching is carried out by the way the teacher applies the concept of learning so that children are more excited, and there are also things that need to be considered and prepared before learning so that learning objectives are achieved properly. Third, the role as a guide is carried out in a way, the teacher must always accompany, direct the children. The teacher guides the child to be able to solve the problems that the child faces. Teachers help children so that children can recognize their strengths and weaknesses by providing activities to children. To increase children's self-confidence, teachers guide children by providing help explaining what children should do. Fourth, the role of assessing is carried out by assessing the attitudes displayed by children using a daily assessment format accompanied by certain criteria that are in accordance with assessment standards for early childhood.